Co4S3/NixS6(7 ≥ x ≥ 6)/NiOOH in-situ encapsulated carbon-based hybrid as a high-efficient oxygen electrode catalyst in alkaline media. (20th September 2016) - Ma, Xiu-Xiu; He, Xing-Quan
Graphical abstract: A highly active bifunctional catalyst has been fabricated by simultaneously encapsuling Co4 S3, Nix S6 (7 ≥ x ≥ 6) and NiOOH nanocrystals on interpenetrated 3D nitrogen-doped graphene-carbon nanotubes (NGC) composite support through an in-situ hydrothermal method. Abstract: Designing highly active oxygen electrode catalysts in unitized regenerative fuel cells is of urgent importance with the development of new energy techniques. Herein, an advanced NGC@Co4 S3 /Nix S6 (7 ≥ x ≥ 6)/NiOOH hybrid by simultaneously encapsuling Co4 S3, Nix S6 (7 ≥ x ≥ 6) and NiOOH nanocrystals on 3D nitrogen-doped graphene-carbon nanotubes (NGC) composite support was fabricated via an in-situ hydrothermal method. Cyclic votammetry (CV), rotating disk electrode (RDE), rotating ring disk electrode (RRDE) and current-time chronoamperometric response were employed to examine the electrochemical performance of the materials. As a consequence, the obtained catalyst not only achieved excellent activity for oxygen reduction reaction, such as similar kinetic parameters compared with 20 wt% Pt/C, but also possessed better durability. Furthermore, our proposed catalyst displayed considerable oxygen evolution reaction properties in comparison with RuO2, like closed overpotential at the current density of 10 mA cm −2 and good stability after 200 cycles of testing. The outstanding electrochemical performance can be ascribed to the good conductivity and large specific surface area of the substrate with interpenetrated structure and the synergistic couplings between multiple active sites of metallic nanocrystals and NGC building blocks.